2008
DOI: 10.1007/s10853-008-2698-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aqueous aging on the mechanical properties of P40Na20Ca16Mg24 phosphate glass fibres

Abstract: Hemiketal. -Title compounds (II) containing a five-membered hemiketal are stereoselectively synthesized from acetylmethyl sugars (I). These products can be further transformed into different pyridine systems. -(WANG, H.; LUO, H.; MA, X.; ZOU, W.; SHAO*, H.; Eur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
40
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 8 publications
8
40
0
Order By: Relevance
“…4 and 5. Other authors in the literature investigated the influence of a heat treatment on the dissolution of phosphate glass fibres, and found similar results [38][39][40]. Choueka et al [38] studied the influence of heat treatments on the dissolution of phosphate glass fibres containing zinc and iron.…”
Section: Dissolution Tests On Glass Fibresmentioning
confidence: 70%
See 3 more Smart Citations
“…4 and 5. Other authors in the literature investigated the influence of a heat treatment on the dissolution of phosphate glass fibres, and found similar results [38][39][40]. Choueka et al [38] studied the influence of heat treatments on the dissolution of phosphate glass fibres containing zinc and iron.…”
Section: Dissolution Tests On Glass Fibresmentioning
confidence: 70%
“…Cozien-Cazuc et al [39] found that the annealing treatment re-duced the dissolution of glass fibres with composition 40P 2 O 5 -20Na 2 O-16CaO-24MgO (mol.%) in distilled water, with a differ-ence of an order of magnitude in the dissolution rate calculated on the first 24 h. The lower dissolution rate of the annealed fibres could be due to stabilization of the glass structure by the relieving of the residual stresses arising from drawing. Cozien-Cazuc et al [40] proposed that the annealed fibres, losing part of the oriented structure imparted by the fibre drawing via relaxation of the poly-meric chains, have a more durable structure, less susceptible to stress corrosion effects.…”
Section: Dissolution Tests On Glass Fibresmentioning
confidence: 99%
See 2 more Smart Citations
“…Abou Neel et al experienced a similar peeling effect for iron containing fibres 7 . This peeling effect in fibres was suggested to be due to the differential hydration between surface and bulk layers leading to tensile forces and subsequent cracking 48 .…”
Section: Discussionmentioning
confidence: 99%